CT Assessment of Woodworkers’ Nasal Adenocarcinomas Confirms the Origin in the Olfactory Cleft - Georgel, T.; Jankowski, R.; Henrot, P.; Baumann, C.; Kacha, S.; Grignon, B.; Toussaint, B.; Graff, P.; Kaminsky, M.C.; Geoffrois, L.; Vignaud, J.M. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Endoscopic endonasal surgery let us observe that woodworkers’ nasal adenocarcinomas originate in the olfactory cleft. Our aim was the identification of CT imaging features that corroborate the olfactory cleft as the site of origin for woodworkers’ adenocarcinoma.MATERIALS AND METHODS: We designed a retrospective study to compare CT scans of 27 unilateral olfactory cleft adenocarcinomas with 30 cases of nasosinusal polyposis (NSP) and 33 healthy sinus controls. Enlargement of the olfactory cleft, lateralization of the ethmoidal turbinate wall, and contralateral bulging of the nasal septum were measured on coronal scans passing through crista galli and posterior half of both ocular globes. Comparisons have been performed by using analysis of variance and the Bonferroni procedure.RESULTS: The nasal septum was significantly bulging across the midline in adenocarcinoma (4.6 ± 3 mm; range, −0.1–13.7 mm) compared with NSP (0.7 ± 1 mm; range, −2.1–2.3 mm) or healthy sinus controls (0.5 ± 1 mm; range, −1.2–2 mm) (P < .001). The olfactory cleft was significantly wider in adenocarcinoma (15.1 ± 4.5 mm; range, 8.6–25.7 mm) than in NSP (3.6 ± 0.4 mm; range, 2.8–4.6 mm) or healthy sinus controls (3.3 ± 0.7 mm; range, 1.4–4.6 mm). The ethmoidal labyrinth width was significantly smaller on the pathologic side in adenocarcinoma (7.2 ± 2.7 mm; range, 3.2–14.2 mm) than in the control groups (P < .001). Whereas the angle between the conchal lamina and vertical midline was close to zero degrees in NSP (0.03 ± 2.25°; range, −5°–3°) and healthy sinus controls (0.45 ± 2.13°, range, −5°–5°), it reached 39.76 ± 13.83° (P < .001) in adenocarcinoma.CONCLUSIONS: Radiologists should suspect nasal adenocarcinoma on sinus CT scans showing a unilateral expanding opacity of the olfactory cavity.